LIFE EXPERIENCES OF MALE SEX MEN (MSM) WITH POSITIVE HIV/AIDS STATUS IN THE WORK AREA OF SERANG CITY HEALTH CENTER - Rahmawati, Dewi; Latifah, Husnul (Journal of Islamic Nursing, 2021)
AbstractThe male sex men group is the largest contributor to the increasing incidence of HIV/AIDS. The purpose of this study is to explore The Life Experience of MSM With Positive HIV/AIDS Status in the Work Area of the Serang City Health Center in 2021. We used phenomenological data analysis with Collaizi’s approach. The sampling technique was purposive sampling based on inclusion criteria and the number of samples determined by data saturation, with in-depth interviews for five participants using mobile phone communication tool. The results showed new insights themes: Falling into the MSM world, MSM sexual world, desire to repent, MSM physical changes with PLWHA, fear of God, and self-stigma. There’s need to provide intensive approach in the form of more innovative education based on spiritual content with the MSM community, educating adolescents about HIV/AIDS prevention, protecting adolescents from the use of gadgets, and improving communication between parents and children. Keywords: HIV/AIDS, Life Experiences, MSM